Pengaruh Penggunaan Benih Bersertifikat Terhadap Produksi dan Efisiensi Teknis Usahatani Kentang di Kecamatan Pangalengan (Jurnal Agribisnis Indonesia, 2022)
The average food consumption for potato commodities in Indonesia is 2.20 kg/capita/year, an increase of 9% from 2013. The need for potato consumption will increase as Indonesia's population increases. The growth rate of potato production is lower than that of potato consumption; therefore, it is necessary to increase potato productivity. The productivity level of potatoes in Indonesia is still low and fluctuates, with an average potato productivity of 18.23 tons/hectare. Increasing potato productivity can be done by increasing technical production efficiency or using certified seeds. The purpose of this study is to analyze the effect of using certified seed on the production and technical efficiency of potato farming in the Pangalengan district as one of the potato production centers in Bandung Regency. The technical efficiency analysis of the potato crop was performed using the Cobb-Douglas Stochastic Frontier Analysis production function with a total of 70 potato farmers as respondents, with details that 30 persons are using certified potato seed and 40 persons are using not certified potato seed. The results indicate that using certified potato seed has increased potato production. Overall, the average technical efficiency of potato production in the Pangalengan district is 70.10%, which means efforts to improve efficiency are still required. There is no significant difference in technical efficiency between potato farms using certified seed and not certified seed which means using certified potato seed has yet to be able to increase the technical efficiency of potato farms. One of the factors that significantly affect technical efficiency is land ownership status.